IDENTITAS TOKOH PRIBUMI DALAM CERPEN PENUNJUK JALAN KARYA IKSAKA BANU: KAJIAN PASCAKOLONIAL HOMI K. BHABHA - Abdullah, Risen Dhawuh; Rabbani, Ilham (MIMESIS, 2022)
This study aims to uncover an Indigenous character named Oentoeng in the short story “Penunjuk Jalan”. The short story is one of Iksaka Banu's works contained in the book Semua untuk Hindia. The identity of the character that is trying to be dismantled includes hybridity, mimicry, and ambivalence. The theory used in this study is the postcolonial theory initiated by Homi K. Bhabha. The study used a qualitative descriptive method. There are three findings in this study. First, the identity of Oentoeng is a hybrid. Oentoeng absorbs Western values continuously, namely from his upbringing, education, and his association in the Dutch family environment. Second, mimicry as mockery by the character can be seen from three aspects, specifically the ability to speak Dutch, possess Western medical knowledge, and to be able to devise a strategy of rebellion that made the VOC troubles as invaders. Third, Oentoeng's attitude of wanting to be angry and willing to provide assistance, treatment, and entertainment to the Dutch doctor and his porter who had an accident could be interpreted as a form of ambivalence in the Indigenous character.